2016
DOI: 10.5306/wjco.v7.i2.220
|View full text |Cite
|
Sign up to set email alerts
|

Symptom management during and after treatment with concurrent chemoradiotherapy for oropharyngeal cancer: A review of the literature and areas for future research

Abstract: Patients with locally advanced oropharyngeal cancer are at risk for poor outcomes due to the multi-modal nature of treatment and the potential for treatment-related toxicity. Although treatment with concurrent chemotherapy and radiotherapy has drastically reduced the need for a debilitating and disfiguring surgery, treatment related toxicities are often difficult to control. Acute toxicities include mucositis, skin desquamation, depression, cachexia, fatigue and nausea and vomiting. Failure to control these sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 92 publications
0
14
0
1
Order By: Relevance
“…The treatment of head and neck cancer (HNC) has evolved over the last several decades, with an increased emphasis placed on multimodality management. Despite advances in the management of HNC, treatment-induced toxicities that compromise dietary intake and nutritional status remain a common complication in HNC patients [ 1 ]. Previous studies have suggested that at diagnosis, 42–77% of HNC cancer patients experience malnutrition which is exacerbated over the course of cancer treatment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of head and neck cancer (HNC) has evolved over the last several decades, with an increased emphasis placed on multimodality management. Despite advances in the management of HNC, treatment-induced toxicities that compromise dietary intake and nutritional status remain a common complication in HNC patients [ 1 ]. Previous studies have suggested that at diagnosis, 42–77% of HNC cancer patients experience malnutrition which is exacerbated over the course of cancer treatment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although HNC cases make up a small percentage of all new cancers in the United States (3%), the survival rates have been steadily increasing in recent years with 5year survival estimated at 65% for oral and pharyngeal cancers and 60% for laryngeal cancers [1,2]. With an increase in survival and intensification of RT with concurrent chemotherapy, there is heightened awareness of the supportive care needs of HNC survivors [3]. A safe and efficient swallow is required for optimal quality of life, nutrition, and to prevent aspiration.…”
Section: Introductionmentioning
confidence: 99%
“… 1 At present, no effective pain treatment without substantial side effects exists for patients with severe oral mucositis pain, and in many patients treated with high-dose opioids there is a lack of sufficient pain relief. 8 …”
Section: Introductionmentioning
confidence: 99%